ANALISIS KEBUTUHAN AIR IRIGASI MENGGUNAKAN METODE CROPWAT VERSION 8.0 - Hanan Shalsabillah; Khairul Amri; Gusta Gunawan (Universitas Bengkulu, 2019)
The Irrigation Area of Air Nipis is located in Regency of South Bengkulu at Bengkulu Province with irrigation area 3.116 Ha. Planning and management of irrigation systems is one of the important steps to determine the irrigation water requirement as a whole. The purpose of this research is aim to analyze the water requirement to get value prediction of minimum and maximum irrigation water requirement in irrigation area of Air Nipis using the CROPWAT Version 8.0 method. Irrigation water requirements obtained from CROPWAT Version 8.0 are based on climate data, soil data and plants.The parameters that were reference plant evapotranspiration, effective rainfall, soil treatment, soil data, and plants. The results of the research showed that the maximum irrigation requirement for calculation using CROPWAT 8.0 software occurred in the first 10 days of December (14,49 m3/sec), while the minimum irrigation water requirements for CROPWAT 8.0 occurs in mid to end March (0,04 m3/sec).